The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/s12935-014-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Chemokine (C-X-C) ligand 1 (CXCL1) associated with tumor progression and poor prognosis in hepatocellular carcinoma

Abstract: BackgroundMany studies support that chemokine (C-X-C motif) ligand 1 (CXCL1) regulate tumor epithelial-stromal interactions involving in tumor growth and invasion. However, limited studies have been conducted on the expression and function of the CXCL1 gene in hepatocellular carcinoma (HCC).MethodsThe mRNA and protein level expression of CXCL1 was examined in HCC tissues and cell lines. The expression of CXCL1 was correlated with clinicopathological features and follow-up data. Overexpression approaches were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Immunostainings were evaluated by two experienced pathologists who were blinded to the clinical data reviewed the stained tissue sections, using the semiquantitative scoring system linking the staining intensity with the percentage of positive cells, according to the previous studies [21,22]. The intensity was classified as follows: 0, negative staining; 1, weak staining; 2, moderate staining; and 3, strong staining.…”
Section: Cell Culturementioning
confidence: 99%
“…Immunostainings were evaluated by two experienced pathologists who were blinded to the clinical data reviewed the stained tissue sections, using the semiquantitative scoring system linking the staining intensity with the percentage of positive cells, according to the previous studies [21,22]. The intensity was classified as follows: 0, negative staining; 1, weak staining; 2, moderate staining; and 3, strong staining.…”
Section: Cell Culturementioning
confidence: 99%
“…Subsequently, it affects the NF-κB downstream molecules via a decrease in anti-apoptotic B-cell lymphoma (Bcl)-2 and an increase in pro-apoptotic Bcl-2-like protein 4 (Bax) and Bcl-2 homologous antagonist/killer (20). Chemokine (C-X-C motif) ligand 1 upregulation may contribute to both the development and progression of HCC, and this effect may be associated with increased proliferation and invasiveness mainly via regulating NF-κB expression (21). The mechanism of HCC metastasis may mediate through cross-talk between the NF-κB and estrogen receptor (ER) signaling pathways (22).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large number of genes are increased by the Try‐19 phosphorylation of SRSF1 (): chemokine (C‐X‐C) ligand 1 ( CXCL1 ), activating transcription factor 5 ( ATF5 ), and ATP/GTP binding protein‐like 2 ( AGBL2 ). Studies showed elevated CXCL1 is associated with tumor progression and poor prognosis in cancers; and the overexpression of ATF5 or AGBL2 enhances malignancy in cancer cells . The mechanisms of SRSF1 within different cellular compartments need to be further studied.…”
Section: Discussionmentioning
confidence: 99%